Contextual Approach to Improve Mathematics Learning Outcomes in Fractional Arithmetic Operations - S. Sulasmi (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
This study aimed to improve mathematics learning outcomes in fractional arithmetic operations in fourth grade students of MI Yasin, Tebing Tinggi city and to see how a contextual approach can improve mathematics learning in fractional arithmetic operations material. The contextual approach accommodates learning that is in accordance with the real life and daily lives of students. Observations in everyday life are very important in understanding mathematical concepts. This research was investigated using classroom action research to improve learning outcomes for grade IV MI Yasin, Tebing Tinggi city. The subjects of this classroom action research are fourth grade students in the even semester of the 2021/2022 academic year at MI Yasin, Tebing Tinggi city. The research was carried out in two cycles. Data were collected by means of a written test in the form of an essay consisting of 10 questions, interviews, and observations. Data were analyzed quantitatively and qualitatively. The results of the study can be concluded that there is an increase in mathematics learning outcomes in fractional arithmetic operations in fourth grade students at the MI Yasin, Tebing Tinggi city and the contextual approach has an effect on improving these learning outcomes.